2013
DOI: 10.1371/journal.pone.0055435
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination to Conserved Influenza Antigens in Mice Using a Novel Simian Adenovirus Vector, PanAd3, Derived from the Bonobo Pan paniscus

Abstract: Among approximately 1000 adenoviruses from chimpanzees and bonobos studied recently, the Pan Adenovirus type 3 (PanAd3, isolated from a bonobo, Pan paniscus) has one of the best profiles for a vaccine vector, combining potent transgene immunogenicity with minimal pre-existing immunity in the human population. In this study, we inserted into a replication defective PanAd3 a transgene expressing a fusion protein of conserved influenza antigens nucleoprotein (NP) and matrix 1 (M1). We then studied antibody and T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…A major cause of the need for product-specific optimisation of adenovirus vector production processes is the fact that some transgenes have a marked impact upon the growth of adenovirus vectors [20]. We and others have previously reported that viruses carrying such 'toxic' transgenes can be rescued by incorporating 'tet operator' elements in the transgene promoter and growing the virus in cells such as HEK293 T-Rex (ThermoFisher) and Procell 92 which repress expression from such modified promoters [20,21,32,33]. Unfortunately however, such cell lines have not been widely accessible for GMP manufacture in suspension culture.…”
Section: Vectors Of Three Serotypes Carrying Three Antigen Transgenesmentioning
confidence: 99%
“…A major cause of the need for product-specific optimisation of adenovirus vector production processes is the fact that some transgenes have a marked impact upon the growth of adenovirus vectors [20]. We and others have previously reported that viruses carrying such 'toxic' transgenes can be rescued by incorporating 'tet operator' elements in the transgene promoter and growing the virus in cells such as HEK293 T-Rex (ThermoFisher) and Procell 92 which repress expression from such modified promoters [20,21,32,33]. Unfortunately however, such cell lines have not been widely accessible for GMP manufacture in suspension culture.…”
Section: Vectors Of Three Serotypes Carrying Three Antigen Transgenesmentioning
confidence: 99%
“…Moreover, a single immunization with ChAd68 induced long-lasting protection against rabies virus by the induction of neutralizing antibodies in nonhuman primates (47). The Ad vector PanAd3, which was isolated from bonobos and which was engineered to express an influenza A virus matrix 1 and nucleoprotein fusion antigen, provided significant protection against a lethal dose of a highly pathogenic challenge influenza virus in mice (48). The novel rhesus monkey adenovirus vectors described in the present study represent a new class of vaccine vectors with unique advantages and distinct biology.…”
Section: Figmentioning
confidence: 99%
“…In addition to the use of rare species human Ads, the issue of high seroprevalence of NAbs to Ad5 in humans can be circumvented by using non‐human Ads, such as those derived from non‐human primates [50,51]. Although there is a high degree of phylogenetic relatedness between Ads derived from different primate hosts,[52] sequence homology within the hypervariable regions (HVRs) of the hexon, the major antigenic target of NAb to Ads[39,53] is more divergent,[54] allowing them to evade pre‐existing immunity in humans.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%